Indigenous people and climate change : causes of flooding in the Bolivian Amazon and consequences for the indigenous population - Canedo, Gabriela (CLACSO, 2021)
The paper discusses the relationship between climate changes and indigenous peoples. To this aim we will focus our research on the effects of the rains in the Department of Beni (Bolivia). This region suffers “monsoon-like” attacks every year which manifest themselves in frequent rains, flooding and main rivers breaking their banks, resulting in extreme flooding. Nevertheless, the historical floods that occurred in 2014 were devastating